Landscape techniques for erosion control and slope stabilization - Asiedu, Joel Bernard Kofi (2011)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of Master of Science degree in Landscape Studies.